Automatic Railway Crossing Using Arduino - DhanushReddy KN, Ganangalla Jeevan Kumar, Darshan B, Gopi Krishna R, Vinay NA (International Journal of Advanced Science and Technology, 2020)
The Automatic Railway crossing using Arduino Project makes use of an Arduino UNO to manage the whole circuit. Two DC motors are acquainted with open and shut the railway gates. The foremost objective is to shut the railway gates when the train approaches it, so on block vehicles from going across the track. Within the rapidly flourishing countries accidents within the unmanned level crossings are increasing day by day. No fruitful steps are taken to the current point in these areas. Our project deals with automatic railway gate control at intersection replacing the gates operated by the gatekeepers. By employing the automated railway gate control at the amount crossing the arrival of the train is detected by the sensors placed within the side of tracks. Hence the time that it’s closed could be a smaller amount compared to the operated by hand gates.